Thalamic oscillatory dysrhythmia and disrupted functional connectivity in thalamocortical loops in perinatal stroke - Anton Rogachov; Helen L. Carlson; Amanda Robertson; Trish Domi; Adam Kirton; Nomazulu Dlamini (Scientific Reports)
Abstract Periventricular venous infarction (PVI) is a subtype of perinatal stroke localized to subcortical white matter occurring before 34 weeks of gestation. An emerging body of literature has reported life-long motor impairments and compromised quality of life in patients with PVI. However, there remains a paucity of foundational knowledge regarding the underlying neurobiological mechanisms that underpin these outcomes. Recent studies (Ferradal et al. in Cereb Cortex 29:1218–1229, 2019) in brain imaging suggest that healthy development of thalamocortical connections is instrumental in coordinating brain connectivity in both prenatal and postnatal periods given the central role the thalamus and basal ganglia play in motor circuitry. Therefore, we provide a regional and cross-network approach to the analysis of interactive pathways of the thalamus, basal ganglia, and cortex to explore possible neurobiological disruptions responsible for clinical motor function in children with PVI. A resting-state fMRI protocol was administered to children with left periventricular venous infarction (PVI) (n = 23) and typically developing children (TDC) (n = 22) to characterize regional oscillatory and thalamocortical disturbances and compare them to clinical motor function. We hypothesized that PVI would affect resting-state measures of both regional and global brain function, marked by abnormally high amplitudes of regional oscillatory activity, as well as lower local and cross-network communication. Using a combination of robust functional metrics to assess spontaneous, oscillatory activity (Amplitude of Low-Frequency Fluctuations [ALFF] and fractional ALFF), as well as local (Regional Homogeneity [ReHo]) and cross-network connectivity (Degree Centrality [DC] and Functional Connectivity [FC]). We found that compared with TDC, children with PVI exhibited higher levels of ALFF, and these functional differences were associated with the severity of motor impairment. Moreover, the thalamus in children with PVI also showed lower connectivity in relaying thalamocortical pathways. These disruptions in thalamocortical pathways from the thalamus were localized to the medial prefrontal cortex (mPFC), a key hub of the default mode network). Collectively, our findings suggest that heightened levels of regional, oscillatory activity in the thalamus may disrupt more widespread thalamocortical cross-network circuity, possibly contributing to motor impairments in children with PVI.